Investigating the Social Aspects Early Medieval Mortuary Practice - Sayer, Duncan (History compass, 2013)
Pre-Christian early medieval cemeteries are rich archaeological sites; they contained burials with weapons, jewellery and pottery vessels. These sites also show some structured organisation - clusters of rich inhumations, rows of graves or differently oriented burials positioned adjacent to earlier features. But the interpretation of these sites has not always been holistic; archaeologists across Europe have developed different theoretical traditions and emphasised different types of evidence. This paper will describe some of these traditions as they relate to social interpretations while emphasising the multi-scaled nature of early medieval culture. Indeed individuals, sites and regional level interpretations are all important ways to understand the social aspects of mortuary practice and it is by combining evidence and learning from different traditions that it might be possible to understand the human experience of the ancient past.